Attitudes Toward Collaboration Among Practitioners in Newly Established Medical Homes: A Survey of Nurses, General Practitioners, and Specialists. (November 2016) - Alcusky, Matthew; Ferrari, Luciano; Rossi, Giuseppina; Liu, Mengdan; Hojat, Mohammadreza; Maio, Vittorio
The objective was to evaluate the attitudes toward collaboration of nurses, general practitioners (GPs), and specialists practicing in newly established Medical Homes (MHs) in Parma Local Health Authority (LHA), Emilia-Romagna region, Italy. The 15-item Jefferson Scale of Attitudes Toward Physician-Nurse Collaboration was administered electronically to 172 physicians (66 GPs, 106 specialists) and 113 nurses practicing in 12 MHs. In all, 191 surveys (45 GPs, 59 specialists, 87 nurses) were completed (67% response rate). The mean total score among nurses (51.5, standard deviation [SD] = 3.7) reflected a significantly ( P < .01) more positive attitude toward collaboration compared with GPs (47.8, SD = 4.6) and specialists (45.3, SD = 7.7). Discrepancies in attitudes are concerning because conflicting perceptions of professional roles may impede a successful transition to integrated care within MHs in Parma LHA. Internationally, further research into understanding interprofessional relationships within MHs is needed to inform policy and build a necessary culture of team-based care.